Role of brachytherapy in the treatment of localized prostate cancer - A. D. Kaprin; V. N. Galkin; S. A. Ivanov (Biomedical Photonics)
The review is devoted to application of brachytherapy for treating the localized prostate cancer (PC). Statistics for incidence and detectability of this pathology and its dynamics for recent years are represented. Brief analysis of other methods which are conveniently used for treatment of PC, such as radical prostatectomy and external-beam radiotherapy, was performed. Advantages and disadvantages of these methods have been discussed. Brief history about the development of brachytherapy from first experience to wide-spread use in clinical practice is reported. The detailed review of series of large trials from Russia and other countries for efficiency and safety of brachytherapy in patients with prostate cancer for recent 15 years is also represented. Two types of brachytherapy in current clinical oncology i.e. low-dose technique with permanent implantation of microsources and high-dose temporary isotope implantation, specifics of its application in different groups of patients have been described. The procedure of brachytherapy and its three main steps i.e. planning, implantation and control assessment after implantation have been characterized in details. The conclusion about benefits of using of brachytherapy in the treatment of prostate cancer as minimally invasive and efficient method was made.